Karakteristik Struktur Anatomi Kayu Kuku (Pericopsis mooniana Thwaiters) The Anatomical Characteristics of Pericopsis mooniana Thwaiters - I Ketut N Pandit (Masyarakat Peneliti Kayu Indonesia, 2005)
The objective of this research is to observe the anatomical characteristics of Pericopsis mooniana Thw. Pericopsis consists of 5 species and Pericopsis mooniana Thw is one of those 5 species, which is developed and planted in PT. INHUTANI UNIT II South Kalimantan since 1987. Two various permanent slides were prepared for microscopic study. The Schultze method was used for preparing maceration slides and staining sections with safranin for microtom slides.The result showed that macroscopic characteristics of heartwood was yellowish-brown when fresh, turning to brown, dark brown or dark golden brown upon exposure, usually with irregular darker streaks. Texture fine to moderately coarse, ripple marks distinct. Microscopic characteristics of growth rings if discernible were marked by marginal, interrupted parenchyma bands and or slight difference in vessel diameter. Vessel diffuse at 8-13/mm2, usually solitary and in radial multiples of 2 3, 115 118 mm in tangential diameter. Fibers 1.0 1.3 mm long, thick-walled approximately 5.0 mm. Parenchyma winged aliform to confluent, connecting a few vessels, apotracheally diffuse in aggregates. Rays 2 3 seriate 234 238 mm high, homocellular. Pericopsis mooniana Thw. timber is very attractive hardwood, it has decorative use and used for cabinetwork, furniture and face veneer